A new species of Kamimuria (Plecoptera, Perlidae) from the Russian Far East - Teslenko, Valentina A. (Zootaxa, 2006)
A new species of Kamimuria, K. lyubaretzi (Plecoptera, Perlidae) from the Russian Far East is described and illustrated for the first time. The description includes all life stages and both sexes. Distributional data are presented.